LEARNING ELLIPTICAL SENTENCES THROUGH DIAGRAMMING TO THE ELEVENTH GRADE STUDENTS - Putri Muntamah, Nining Dwi; Oktarini, Dessi; Deviyanti, Ivana; Muslim, Andika (Jurnal Ilmiah Bina Bahasa, 2018)
The objective of this research was to find out whether or not learning elliptical sentences through diagramming is effective. The population of this investigation was all of the eleventh grade students of SMA Pembina Palembang. It consisted of 147 students. The sample was two classes chosen through the cluster random sampling. One was treated as the experimental group and the other as the control group. The data were collected through the written test and were analyzed by using the percentage formula and t-test. Based on the result of the data analysis, it shows that the t-obtained was 4.547 and the t-critical value was 1.711 from degree of freedom (df) = 24. The t-obtained was greater than the critical value or 4,547>1.711. The null hypo research was rejected and alternative hypo research was accepted. In conclusion, learning elliptical sentences through diagramming was effective.